It pays to be active on many foreign markets profitability in German multi-market exporters and importers from manufacturing industries - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2017)
This paper provides the first empirical evidence on the link between the number of foreign markets (where a market is defined as the combination of one traded good and one country traded with) a firm is active on and its profitability. We find that in German manufacturing industries the profitability of a firm increases when the number of markets a firm exports to or imports from increases. The extra costs associated with being active on more foreign markets tend to be smaller than the extra benefits. It pays to be active on many foreign markets.
Keywords: F14; 330; Exports; Imports; Number of foreign markets; Profitability; Germany